Efeito da cadência de pedalada sobre as respostas metabólica e cardiovascular durante o exercício incremental e de carga constante em indivíduos ativos - Denadai, Benedito Sérgio [UNESP]; de Araújo Ruas, Vinícius Daniel [UNESP]; Figueira, Tiago Rezende [UNESP] (FapUNIFESP (SciELO), 2005)
The main purpose of this study was to analyze the effect of the pedaling cadence (500 × 100 rpm) on the heart rate (HR) and the blood lactate response during incremental and constant workload exercises in active individuals. Nine active male individuals (20.9 ± 2.9 years old; 73.9 ± 6.5 kg; 1.79 ± 0.9 m) were submitted to two incremental tests, and to 6-8 constant workload tests to determine the intensity corresponding to the maximal steady state lactate (MLSSintens) in both cadences. The maximal power (Pmax) attained during the incremental test, and the MLSSintens were significantly lower at 100 rpm (240.9 ± 12.6 W; 148.1 ± 154.W) compared to 50 rpm (263.9 ± 18.6 W; 186.1 ± 21.2 W), respectively. The HRmax did not change between cadences (50 rpm = 191.1 ± 8.8 bpm; 100 rpm = 192.6 ± 9.9 bpm). Regardless the cadence, the HRmax percentage (70, 80, 90, and 100%) determined the same lactate concentrations during the incremental test. However, when the intensity was expressed in Pmax percentage or in absolute power, the lactate and the HR values were always higher at highest cadences. The HR corresponding to MLSSintens was similar between cadences (50 rpm = 162.5 ± 9.1 bpm; 100 rpm = 160.4 ± 9.2 bpm). Based on these results, it can be conclude that regardless the cadence employed (50 × 100 rpm), the use of the HR to individualize the exercise intensity indicates similar blood lactate responses, and this relationship is also kept in the exercise of constant intensity performed at MLSSintens. On the other hand, the use of the Pmax percentages depend on the cadence used, indicating different physiological responses to a same percentage.
Effects of the pedaling cadence on metabolic and cardiovascular responses during incremental and constant workload exercises in active individuals
Keywords: Cadence; Cycling; Exercise intensity; Heart rate; Lactate; lactic acid; adult; cardiovascular response; controlled study; cycling; exercise intensity; exercise physiology; exercise test; heart rate; human; human experiment; lactate blood level; male; metabolic regulation; normal human; steady state; training; workload